Design Support to steer Creative Wicked Problem Solving Processes with Knowledge Management and Artificial Intelligence - Langenhan, C; Eisenstadt,, V; Petzold,, F; Althoff,, K (Journal of Model Based Research, 2019)
As the complexity of building tasks and requirements increases, designers often find themselves confronted with interdisciplinary problems that go beyond the specific challenges and methods of architecture. The iterative nature of the design process results in a continuous exchange between creative, analytical and evaluative activities, through which the designer explores and identifies promising design variants. The ability to compare and evaluate relevant reference examples of already built or designed buildings helps designers to assess their own design and informs the design process.
Keywords: Modelling